An Overview of Vulnerability Criteria for Pure Loss of Stability - Akyildiz, Hakan (İstanbul Teknik Üniversitesi, 2022)
This paper presents the current state of development of the second generation of intact stability criteria based on pure loss of stability. The concept of a multi-tiered evaluation process is based on the physics of the stability failures addressing the interaction between hull and waves in a seaway condition. After having a brief review of the recent history of related IMO development, the paper describes the framework of the new criteria in which they are complementary to the existing IMO criteria. The new criteria can be applied only to those designs that may be susceptible to one of the modes of stability failure using a set of formalized procedures of vulnerability checks. The ideas, proposals and justifications of these procedures represent the novel contents of the paper. Finally, the paper reviews pure loss of stability as a failure mode for performance-based criteria including restoring arm variation and critical stability related problems in waves.
Keywords: Deniz Mühendisliği; Pure Loss of Stability; Multi-tiered approach; Vulnerability Criteria; Intact Stability; Maritime Engineering